Pulmonary arterial hypertension in childhood: an unsual presentation with fibrosing mediastinitis - Teopompi, Elisabetta; Tchana, Bertrand; Chetta, Alfredo; Aiello, Marina; Sgrignoli, Marta; Carano, Nicola; Agnetti, Aldo (Acta Biomedica Atenei Parmensis, 2014)
Acquired stenosis of normally connected pulmonary veins is a rare condition in children, usually associated with mediastinal processes. It may present later with a less specific clinical picture, symptoms and signs mimicking chronic lung disease. Fibrosing mediastinitis is a rarer disorder of unknown etiology, although several suspected causes such as granulomatous diseases, characterized by fibrous tissue proliferation within the mediastinum, leading to respiratory and cardiac failure by bronchial obstruction or pulmonary hypertension.